2006
DOI: 10.1111/j.1749-4877.2006.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity decreases as population density declines: Implications of temporal variation in mitochondrial haplotype frequencies in a natural population of Tscherskia triton

Abstract: Although the spatial genetic differentiation that occurs in animal populations has been extensively studied, information on temporal variations in genetic structure and diversity is still lacking, especially for animals with oscillating populations. In the present study, we used the mtDNA D-loop sequence to assess the temporal genetic variation in samples from six successive years for the greater long-tailed hamster, Tscherskia triton. Sampling was carried out between 1998 and 2003 in cropland on the North Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Therefore, we believe there is high genetic diversity existing within three patchy-distributed populations, which indicates high viability leading to fluctuation of hamster populations. At this point, our results are consistent with many previous studies [13], [14], [38], [65]. Gene flow between different populations is usually considered as an important factor leading to high genetic diversity within populations.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we believe there is high genetic diversity existing within three patchy-distributed populations, which indicates high viability leading to fluctuation of hamster populations. At this point, our results are consistent with many previous studies [13], [14], [38], [65]. Gene flow between different populations is usually considered as an important factor leading to high genetic diversity within populations.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 92%
“…When density is high, dispersal rate is also high due to frequent intra-specific attacks [13]. Our previous studies have indicated that genetic diversity of this species was positively associated with its population density [13], [14].…”
Section: Introductionmentioning
confidence: 93%
“…Using RAPD markers, Xie and Zhang (2006) found genetic diversity decreased with population decline in the Greater long-tailed hamster ( Tscherskia triton ) [14]. Dong et al (2010) found that genetic diversity of this species is positively correlated to population density using microsatellite markers [13].…”
Section: Introductionmentioning
confidence: 99%